Severe influenza infection is associated with inflammatory programmed cell death in infected macrophages - Ferreira, André C.; Sacramento, Carolina Q.; Pereira-Dutra, Filipe S.; Fintelman-Rodrigues, Natália; Silva, Priscila P.; Mattos, Mayara; de Freitas, Caroline S.; Marttorelli, Andressa; de Melo, Gabrielle R.; Campos, Mariana M.; Azevedo-Quintanilha, Isaclaudia G.; Carlos, Aluana S.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Influenza A virus (IAV) is one of the leading causes of respiratory tract infections in humans, representing a major public health concern. The various types of cell death have a crucial role in IAV pathogenesis because this virus may trigger both apoptosis and necroptosis in airway epithelial cells in parallel. Macrophages play an important role in the clearance of virus particles, priming the adaptive immune response in influenza. However, the contribution of macrophage death to pathogenesis of IAV infection remains unclear. Methods In this work, we investigated IAV-induced macrophage death, along with potential therapeutic intervention. We conducted in vitro and in vivo experiments to evaluate the mechanism and the contribution of macrophages death to the inflammatory response induced by IAV infection. Results We found that IAV or its surface glycoprotein hemagglutinin (HA) triggers inflammatory programmed cell death in human and murine macrophages in a Toll-like receptor-4 (TLR4)- and TNF-dependent manner. Anti-TNF treatment in vivo with the clinically approved drug etanercept prevented the engagement of the necroptotic loop and mouse mortality. Etanercept impaired the IAV-induced proinflammatory cytokine storm and lung injury. Conclusion In summary, we demonstrated a positive feedback loop of events that led to necroptosis and exacerbated inflammation in IAV-infected macrophages. Our results highlight an additional mechanism involved in severe influenza that could be attenuated with clinically available therapies.